THE INFLUENCE OF LEADERSHIP STYLE AND REWARD SYSTEM ON EMPLOYEE PERFORMANCE AT PT. PERTAMINA GEOTHERMAL ENERGY AREA LAHENDONG - Syalom Mokorimban; Willem J. F. A. Tumbuan; Regina T. Saerang (Universitas Sam Ratulangi, 2023)
To achieve company goals, of course, employees are required to maximize their performance. Performance is something that cannot be separated from the company. Employees are required by the company to be able to contribute or perform well and must also be able to increase productivity within the company because the progress or failure of a company depends on employee performance. In this study, the researchers' objective aligns with those of causal study which is to discover whether or not each of the independent variable components affect the mediating variable and thus the dependent variable. From the perspective of analysis and data collection method, researchers will be using a quantitative data analysis. The purpose of this study is researcher want to examine the influence of leadership style and reward system on employee performance at PT. Pertamina Geothermal Energy Area Lahendong. The data used in this study are primary data of 78 respondents with a questionnaire or questionnaire method. This study using a quantitative method. The method used to examine relationship between the independent variable and the dependent variable is a multiple linear regression method and classical assumption test. The result of this study, indicate that Leadership Style and Reward System Partially and Simultaneously had a positive and significant effect on Employee Performance at PT. Pertamina Geothermal Energy Area Lahendong. Keywords: human resources management, leadership style, reward system, employee performance.